The Fight against the Least Visible Form of Human Trafficking: Trafficking for Child Labour Exploitation - Luz María Puente Aba (Oñati Socio-Legal Series, 2018)
Child trafficking for the purpose of labour exploitation is a difficult phenomenon to detect. It is also not readily definable considering that this specific form of trafficking is closely linked with the phenomenon of forced child labour, and even with the broader occurrence of child labour. A lack of globally reliable data and the convergence of different concepts related to child trafficking for labour exploitation pose significant challenges when trying to regulate the circumstances concerning child work and the criminalisation of trafficking for labour exploitation. This article offers a clear overview of the available data related to all the phenomena, and aims to clarify all the situations involved, defining child work, child labour, forced child labour and child trafficking for the purposes of labour exploitation. Furthermore, this article discusses the possible loopholes and critical issues that could hinder global approaches to resolving these issues.